Adults Followed by Pediatric Subspecialists: A Growing Population in the Pediatric Emergency Department. Issue 2 (February 2022) - Rudloff, James; Gittelman, Mike; Pomerantz, Wendy J.
Abstract : Background: Adults are being seen with increasing frequency in pediatric emergency departments (PEDs), but the drivers behind this increase are unknown. Our primary aim was to compare adults seen in the PED followed by pediatric subspecialists to those who are not. Methods: A retrospective study of patients 21 years or older presenting to the PED of a tertiary care children's hospital was performed from January 2011 through December 2018. Data included patient demographics, PED length of stay, disposition, and any subspecialty clinic encounters at the children's hospital in the prior year. Results: A total of 10, 034 adult encounters were seen in the PED over the study period; 5852 (58.3%) adult PED encounters had preceding pediatric subspecialty clinic visit(s) within a year prior. Pediatric subspecialty adult PED encounters increased by 38.9%, compared with 10.6% for other adults ( P = 0.01). Encounters for pediatric subspecialty adults were significantly longer and more likely to result in admission to the children's hospital. The most common pediatric subspecialists caring for adult patients seen in the PED were hematology/oncology (1655 encounters), neurology (1572 encounters), cardiology (1217 encounters), and gastroenterology (1173 encounters). Conclusions: Pediatric subspecialty adults are presenting to the PED at a greater rate, and they require more time and resources compared with other presenting adults. As frontline providers, PEDs, physicians, and staff must be prepared to address this growing subset of patients driving the increase in adults presenting to the PED.